Participação do córtex insular na formação da memória de reconhecimento social - Cavalcante, Lorena Evelyn Silva (2017)
The insular cortex (IC) receives afferent projections from prefrontal cortex, cingulate gyrus, olfactory bulb, basal nuclei and forms reciprocal connections with important limbic areas: amygdala and entorhinal cortex. These different connections indicate a possible involvement of the insular cortex in the process of learning and memory. Social recognition memory (SRM) is essential for forming social groups, establishing hierarchies and social and affective ties. Despite its importance, the knowledge about the brain structures and the cellular and molecular mechanisms involved in its processing is still scarce. Thus, the present study aimed to verify the participation of NMDA-glutamatergic, D1/D5-dopaminergic, H2-histaminergic, β-adrenergic and 5-HT1A serotoninergic receptors, of the IC, in the consolidation of SRM. For this, male Wistar adult rats (300-330 g) were submitted to stereotaxic surgery for implantation of bilateral cannulae in the IC and, later, to the task of social discrimination. The task consists of 4 consecutive days of habituation to the experimental apparatus, which is an open-field box containing 2 acrilic cilinders, for 20 min. Twenty four hours after the last habituation session, the animals were placed in the open field in the presence of a juvenile (22 days postnatal) for 1 hour (sample phase). After 24 hours, the retention test occurred, for 5 min, in the presence of a juvenile previously met (familiar) and a new juvenile. Animals that received the intra-IC infusion of the antagonist D1/D5, β-adrenergic or 5-HT1A receptor, immediately after the sample phase, impairs the consolidation of SRM. However, this effect was blocked by the concomitant intra-IC infusion of the agonist and the antagonist of the respective receptors. In addition, animals that received intra-IC infusion of the antagonists NMDA and H2 receptors, immediately after the sample phase, were able to consolidate the SRM. The results obtained in the present study suggest that the dopaminergic D1/D5, β-adrenergic and serotonergic 5-HT1A receptors, but not the glutamatergic NMDA and the histaminergic H2 receptors, of the IC, participates in the consolidation of the SRM.